2012
DOI: 10.1186/1472-6920-12-93
|View full text |Cite
|
Sign up to set email alerts
|

Survey of UK radiology trainees in the aftermath of ‘Modernising Medical Careers’

Abstract: BackgroundFollowing implementation of Modernising Medical Careers (MMC) in the UK, potential radiology trainees must decide on their career and apply sooner than ever before. We aimed to determine whether current trainees were sufficiently informed to make an earlier career decision by comparing the early radiology experiences of Traditional and Foundation Trainees.Methods344 radiology trainees were appointed through MMC in 2007/08. This cohort was surveyed online.ResultsResponse rate was 174/344 (51%). Tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This is consistent with other studies reporting that career choice is chiefly dictated by the postgraduate experiences of junior doctors. 11,12 However, the scarcity of foundation and CMT rotations that include dermatology 13 suggests that those undertaking these may have already fostered an interest in dermatology during medical school.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other studies reporting that career choice is chiefly dictated by the postgraduate experiences of junior doctors. 11,12 However, the scarcity of foundation and CMT rotations that include dermatology 13 suggests that those undertaking these may have already fostered an interest in dermatology during medical school.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found Foundation‐Year doctors feel increasingly prepared for their postgraduate posts (Lachish et al, ; Miles et al, ). However, when examining radiology specifically, studies in the United Kingdom and Ireland have found that Foundation‐Year doctors feel their undergraduate radiology education had not adequately prepared them for practice (Nyhsen et al, ; Mair et al, ). The findings of this study differ from this, in that a high proportion of UoN medical school graduates think that MSK radiology teaching was adequate.…”
Section: Discussionmentioning
confidence: 99%
“…Until just a few years ago, radiology training in the United Kingdom was so competitive that candidates would often acquire several years of clinical experience and alternative postgraduate qualifications in other specialties before entering specialized radiology training [13]. One study suggests, however, that between 1974 and 2002, junior doctors choosing to enter radiology after only 1 year of medical training was on the rise, with a steady increase observed from 1993 onward [14].…”
Section: The Clinical Radiologistmentioning
confidence: 99%
“…One study suggests, however, that between 1974 and 2002, junior doctors choosing to enter radiology after only 1 year of medical training was on the rise, with a steady increase observed from 1993 onward [14]. Until 2005, however, it was still the case that a doctor's specialty training would usually begin a minimum of 3 years after graduation from medical school [13].…”
Section: The Clinical Radiologistmentioning
confidence: 99%